Phylogenetic biogeography and classification of the Drosophila montium species group (Diptera: Drosophilidae). Issue 2 (4th March 2018) - Yassin, Amir
Summary: The Drosophila montium group is the largest clade of the subgenus Sophophora consisting of 94 palaeotropical species, whose phylogenetic relationships remain unclear. Here, I used a recent tree inferred from three nuclear genes and one mitochondrial gene for almost half of the species to reconstruct the historical biogeography of the group and propose a comprehensive classification for the totality of its species. The group originated in South-East Asia nearly 20 million years ago (mya), and dispersed to Africa in the Late Miocene. A second northward expansion into East Asia took place in the Pliocene. Based on morphological (male abdominal pigmentation and genitalia) and chorological traits congruent with the molecular tree, I divide the montium group into seven subgroups: parvula, montium, punjabiensis, serrata, kikkawai, seguyi and orosa . The polyphyletic status of some of the previously defined complexes ( auraria, jambulina, serrata, kikkawai and nikananu ) is also resolved.